Maritime networks in the Mycenaean world - Tartaron, Thomas F. (Cambridge: New York Cambridge University Press, 2013)
In this book, Thomas F. Tartaron presents a new and original reassessment of the maritime world of the Mycenaean Greeks of the Late Bronze Age. By all accounts a seafaring people, they enjoyed maritime connections with peoples as distant as Egypt and Sicily. These long-distance relations have been celebrated and much studied; by contrast, the vibrant worlds of local maritime interaction and exploitation of the sea have been virtually ignored. Dr Tartaron argues that local maritime networks, in the form of 'coastscapes' and 'small worlds', are far more representative of the true fabric of Mycenaean life. He offers a complete template of conceptual and methodological tools for recovering small worlds and the communities that inhabited them. Combining archaeological, geoarchaeological and anthropological approaches with ancient texts and network theory, he demonstrates the application of this scheme in several case studies. This book presents new perspectives and challenges for all archaeologists with interests in maritime connectivity.
Includes bibliographical references (p. 297-322) and index.
Keywords: Navigation -- History -- To 146 B.C. -- Greece; Coastal archaeology -- Methodology. -- Greece; Coast changes -- History. -- Greece; Civilization, Mycenaean; Navigation -- History -- To 1500. -- Greece; Commerce -- History -- To 500.; Classical Greek & Roman archaeology; Transportation/General; Greece -- Commerce -- History, Ancient; Aegean Sea -- Navigation -- History -- To 1500.